Definition and diagnosis of small fiber neuropathy: consensus from the Peripheral Neuropathy Scientific Department of the Brazilian Academy of Neurology - Francisco de Assis Aquino Gondim; Amilton Antunes Barreira; Rinaldo Claudino; Márcia Waddington Cruz; Francisco Marcos Bezerra da Cunha; Marcos Raimundo Gomes de Freitas; Marcondes Cavalcante França Jr; Marcus Vinícius Magno Gonçalves; Wilson Marques Jr; Osvaldo José Moreira Nascimento; Acary Souza Bulle Oliveira; Raquel Campos Pereira; et al. (Arquivos de Neuro-Psiquiatria)
ABSTRACT The aim of this study was to describe the results of a Brazilian Consensus on Small Fiber Neuropathy (SFN). Fifteen neurologists (members of the Brazilian Academy of Neurology) reviewed a preliminary draft. Eleven panelists got together in the city of Fortaleza to discuss and finish the text for the manuscript submission. Small fiber neuropathy can be defined as a subtype of neuropathy characterized by selective involvement of unmyelinated or thinly myelinated sensory fibers. Its clinical picture includes both negative and positive manifestations: sensory (pain/dysesthesias/pruritus) or combined sensory and autonomic complaints, associated with an almost entirely normal neurological examination. Standard electromyography is normal. A growing list of medical conditions is associated with SFN. The classification of SFN may also serve as a useful terminology to uncover minor discrepancies in the normal values from different neurophysiology laboratories. Several techniques may disclose sensory and/or autonomic impairment. Further studies are necessary to refine these techniques and develop specific therapies.